An ICT-supported intergenerational knowledge transfer framework for family firms / Sabiroh Md Sabri - Md Sabri, Sabiroh (2017)
In recent years, the world's aging phenomenon has led to the increase number of retirements in organisations. When people leave their organisations, they also take with them their experience, skills and knowledge, hence leaving the organisation to suffer loss of intellectual knowledge, and certainly caused the business's sustainability and continuity to be in danger. This phenomenon has inevitably affected family firms because their survival depends on tacit knowledge possessed by the founder as the source of its competitive advantage. Therefore, to ensure its sustainability, family firms must guarantee that their knowledge is preserved and being transferred to the successor of the business. Many researchers proposed knowledge transfer models which mostly focused on knowledge transfer methods, strategies, and processes to mitigate knowledge transfer barriers, create an optimal knowledge transfer domain for large organisations and inter-organisational knowledge transfer. However, the methods and strategies proposed were found to be ineffective for family firms, thus caused the success of knowledge transfer in family firm to be very low. This research is motivated to provide a platform for family firm to transfer their knowledge from the older generation to the younger generation with the consideration of family firm uniqueness. The qualitative approach was adopted in understanding the characteristics of family business, strategies, and mechanisms used in transferring their knowledge. A case study approach with multiple unit of analysis was use as the strategy of inquiry where data was collected using interview and observation. Data was analysed using content analysis using inductive and deductive approach. The results reveals the unique intergenerational knowledge transfer process, which are the recalling and assembly of knowledge, and the components found in the intergenerational knowledge transfer process which consist of information source, recipient, communication channel, knowledge content, knowledge transfer mechanisms, motivation to source and knowledge recall process. Three issues that hinders the knowledge transfer were also discovered, which are difficulties in recalling knowledge, knowledge loss during transfer and rigid knowledge transfer environment. This research produced an ICT supported intergenerational knowledge transfer framework which integrate the knowledge transfer process, components, issues and technologies. The use of multimedia technology, collaboration technology together with mobile and wireless technology reinforce the framework in demonstrating the comprehensiveness of all the aspects in intergenerational knowledge transfer and uniqueness because it deals with two generations in transferring the knowledge. The development of this framework is crucial to assist family business in ensuring their knowledge received by their successor and subsequently ensure the existence of their family business in the future.